India's Labour Migration to the Kingdom of Saudi Arabia: Issues and Challenges - Alam, Imran; Ahmed, Shahid (Arthshastra Indian Journal of Economics & Research, 2019)
The Indian economy has been benefitted by migration of Indian skilled and unskilled labour to the Kingdom of Saudi Arabia and partly filled its trade account deficit and facilitated in the management of balance of payments even in the period of global crisis. In many states of India such as Kerala, Punjab, etc. where remittances acted as the backbone of the state economy, there has been substantial improvement in the standards of life for migrant labour. Though, remittances play a crucial role in a developing economy like India, but on the other side, it is also true that Indian immigrants face a lot of challenges and exploitation in gulf countries. To keep all these things in mind, the present paper highlighted the issues and problems faced by Indian semi-skilled labour in the Kingdom of Saudi Arabia. The results of the field survey showed that the frequent delay in wage payments was a major problem. The results also showed that the presence of middle men and lack of awareness in semi-skilled labours about their rights were the main causes of issues/problems related to immigrant labour. In the end, the paper suggested that the Government of India must play a pro-active role in solving all these issues.